2008
DOI: 10.1007/s00572-008-0203-4
|View full text |Cite
|
Sign up to set email alerts
|

High compatibility between arbuscular mycorrhizal fungal communities and seedlings of different land use types in a tropical dry ecosystem

Abstract: We conducted this study to explore limitations for the establishment of mycorrhizal associations in disturbed areas of the tropical dry ecosystem in the Chamela region of Jalisco, Mexico. Specifically, we: (1) assessed the diversity and composition of arbuscular mycorrhizal fungal (AMF) communities through spore morphospecies identification in three common land uses (primary forest, secondary forest, and pasture), (2) tested the inoculum potential of the AMF communities and the effect of water stress on the es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 21 publications
0
22
0
9
Order By: Relevance
“…Rodríguez et al (2002) demonstrated that AMF diminishing both leaching and fixation of nutrients, as well as reducing soil erosion since AMF hyphae allow better uptake and mobilization of nutriments to the host, and favour soil aggregation. The symbiotic performance on plant host is equally influenced by hydric status of soil and light availability (Gavito et al, 2008;Shukla et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rodríguez et al (2002) demonstrated that AMF diminishing both leaching and fixation of nutrients, as well as reducing soil erosion since AMF hyphae allow better uptake and mobilization of nutriments to the host, and favour soil aggregation. The symbiotic performance on plant host is equally influenced by hydric status of soil and light availability (Gavito et al, 2008;Shukla et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, several authors agree on the advantages that the AMF inoculation provides on improving root growth, increasing plant survival, reducing the time plants spend in nursery, reducing cost production due to reduction of fertilizer applications, as well as increasing plant quality (Gehring & Connell, 2005;Allen et al, 2003;Hernández & Salas, 2009). Other advantages of AMF inoculation are related to the increase of photosynthetic rate during acclimatization and development of micro-propagated plants, the induction of drought resistance, and the protection of roots against pathogen attack (Ferrera-Cerrato & Alarcón, 2004;Gavito et al, 2008;Shukla et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is similar to the richness reported for other tropical dry ecosystems during different successional stages. Gavito et al (2008) identified a total of 39 AMF species in primary forest, secondary forest and pastures in dry forest ecosystems in the Chamela region, Jalisco state, Mexico. A large number of AMF species (61) have also been reported from other tropical ecosystems encompassing pristine forest, young and old secondary forest, agroforestry systems, croplands and pasture (Stürmer & Siqueira, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have assessed the effects of different types of disturbance on the mycorrhizal status of native tree species in a tropical deciduous forest (Allen, Rincon, Allen, Pérez-Jimenez, & Huante, 1998) or have explored the limitations for the establishment of mycorrhizal associations in disturbed tropical dry ecosystems (Gavito, Pérez-Castillo, González-Monterrubio, Vieyra-Hernández, & Martínez-Trujillo, 2008). Additionally, Camargo-Ricalde, Dhillion, & Jiménez-González, (2003) evaluated the mycorrhizal status of perennial xeric plant species occurring in an arid tropical shrub and tropical deciduous forest; Guadarrama, Castillo-Arguero, Ramos-Zapata, CamargoRicalde and Álvarez-Sánchez (2008) determined the mycorrhizal inoculum potential of the soil under secondary vegetation at different stages of development, and Leal, Siqueira and Stürmer (2013) evaluated how AMF community composition was affected by conversion of tropical amazon forest to pasture.…”
mentioning
confidence: 99%